Forest Sustainability in State Forest Management Plans: A Content Analysis. (2nd January 2022) - Gutierrez Garzon, Alba Rocio; Bettinger, Pete; Abrams, Jesse; Siry, Jacek P.; Mei, Bin
ABSTRACT: A commitment to sustainability is often demonstrated through both management plans and the implementation of practices. We applied content analysis to a sample of state forest management plans from the United States to examine the terms associated with sustainability, and to assess explicit demonstrations of a commitment to sustainable forestry. We expected that the language employed would signal an interpretation of terms associated with forest sustainability. We queried the plans for a list of terms associated with sustainability and analyzed the textual context. Eight categories and 11 subcategories were developed to code the plans for the presence/absence of statements associated with dimensions of sustainability. Our results show that the three dimensions of sustainability are addressed in these forest management plans. Further, certain terms generally associated with sustainability did not appear in the text of the forest management plans sampled. Both, procedural and prescriptive measures seem valid to ensure compliance with management requirements. Differences between regions regarding the use of terms and the emphasis given to each sustainability consideration are evident. Our findings suggest that forest management plans may lack some discursive components that might be important in aiding public understanding of forest management planning to evidence demonstrations of forest sustainability.